Traffic-related pollution history (1994-2014) determined using urban lake sediments from Nanjing, China. - Gengyu Liu (Public Library of Science (PLoS), 2021)
With the development of urbanisation and the increasing number of modern vehicles, traffic contamination has become an important source of environmental pollution. Most previous studies have focused on using roadside soil or plants to determine the spatial pattern of traffic pollutants along roads and the factors that influence this pattern, whereas few studies have reconstructed pollution histories caused by traffic using suitable methods. In this study, two gravity cores were obtained from Qianhu Lake, which is in the Zhongshan tourist area of Nanjing City and is distant from industrial areas. An accurate chronological framework covering the period from 1994 to 2014 was established using the correlation between the variation in grain size of the sediment cores and the variation in annual rainfall in Nanjing City. Moreover, magnetic and chemical parameters were also measured, and the results demonstrated that concentration-related magnetic parameters exhibited different correlations with different heavy metal concentrations. These correlations were significantly positive for Zn, Pb, and Co; weakly positive for Ni; absent for Cr; and negative for V. Combined with statistical data on industrial emissions and private cars in Nanjing City since 1994, the observed variations in magnetic susceptibility, anhysteretic remanent magnetisation, saturation isothermal remanent magnetisation, Zn, Pb, and Co, were controlled by traffic activities in the tourist area but not by industry. Therefore, the variations in these parameters record the traffic pollution history of the study area. Combined with the obtained chronological framework, the traffic-related pollution history could be divided into two stages: 1) from 1994 to 2003, when traffic-related pollution became increasingly serious because of the exponential increase in the number of private cars and the prosperity of tourism; 2) from 2003 to 2014, when traffic-related pollution continuously increased but at a much slower rate than in stage 1. This slower rate of increase was probably related to the maximum carrying capacity of the tourist area and technological innovations in automobile manufacturing, as well as improvements in fuels.